Pelatihan Pembuatan Ekstrak Daun Bidara sebagai Biolarvasida bagi Kader Kesehatan Lingkungan - Nurul Amaliyah; Yulia; Fathmawati (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2024)
Dengue vector eradication requires the active role of environmental health cadres. One of the cadres' activities is to attach chemical larvicide (abate) to water reservoirs in people's homes. Research on the use of biolarvicide has been conducted and has given good results. This community service aims to improve the cadres' ability to eradicate Aedes aegypti larval mosquitoes using biolarvacide. The method of community service is to provide training in making bidara leaf extract and utilising it as biolarvicide. Cadres' knowledge about bidara leaf extract utilisation was measured using questionnaires before and after the training. The data was analysed using a t-test. The results of this community service showed that the caders' knowledge increased on average by 36% after training. The number of free larvae in the environment where cadres live has improved after being given bidara leaf extract in water reservoirs. The Primary Health Centre should increase cadres' knowledge regularly and encourage cadres to utilise the knowledge gained by increasing the number of free larvae.